Pelatihan dan Pendampingan Penyusunan RPP Berbasis Literasi Numerasi Bagi Guru-guru di SD Negeri Buraen 1, Kab. Kupang - Magdalena Wangge (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
One of the main components in the Minimum Competency Assessment, which is a substitute for the National Examination, is Literacy and Numeracy. Teachers need to create literacy and numeracy-based learning to familiarize students, one of which is by compiling a numeracy literacy-based lesson plan. However, in reality, many schools still need to implement this in the field because it is pretty tricky, including for partner schools at public elementary school Buraen 1. The solution offered is to provide teachers with an understanding of literacy and numeracy and how to compile a literacy and numeracy-based lesson plan. This activity is carried out through training and mentoring, where the methods used are lectures, discussions, group work, and individual mentoring. The results were that teachers at public elementary school Buraen 1, South Amarasi District, Kupang Regency, could know how to apply literacy and numeracy to students in the classroom. It is proven by the fact that teachers have been able to compile literacy and numeracy-based lesson plans.